Assessment of the performances of various wave energy converters along the European continental coasts. (15th March 2015) - Rusu, Liliana; Onea, Florin
Abstract: The present work aims to provide a realistic picture of the efficiency along the European continental coasts of ten representative wave energy converters. The main coastal environments targeted are the western sides of Scandinavia, Ireland, UK, Iberian Peninsula and also the Mediterranean and Black seas. In order to evaluate the wave climate corresponding to these coastal areas, several reference points, located at about 50 m water depth, were defined. An analysis of the wave conditions in the target areas has been performed by considering 11-year of hindcast wave data (January 2003–December 2013) provided by the European Centre for Medium-Range Weather Forecasts. At that point, the analysis was focused on the evaluation of the main wave parameters, including the expected average wave power. Thus, for all coastal environments and wave energy converters considered, besides the expected electric power and the capacity factor, some other indicators (as the normalized power) have been also evaluated. The results show that in general the converters with a nominal power greater than 2000 W can generate a significant amount of electricity, compared to the systems rated below 1000 kW, which instead appear to have higher values of the capacity factor, especially during the winter season. Highlights: Wave energy along the European continental coasts is evaluated. Hindcast wave data from ECMWF are considered. Some of the most relevant existent WECs (wave energy converters) are analyzed. Capture widths and capacity factors have been evaluated.